2021
DOI: 10.1177/1478929921998210
|View full text |Cite
|
Sign up to set email alerts
|

Formal Education and Contentious Politics: The Case of Violent and Non-Violent Protest

Abstract: This study investigates the effect that formal education, as a factor of socio-economic development, has on the intensity and forms of political protest. By way of increased socialization of democratic values, increased cognitive understanding of the society at large, and human capital to participate in protests, increases in a country’s level of formal education should theoretically lead to increased levels of peaceful protest. However, increases in formal education are also theorized to play a mitigating rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…At the same time, past studies (Sawyer and Korotayev, 2022) lead us to believe that there may be a qualitative difference between the forms that this protests activity takes; we propose an original theory as to why students would be more likely to join peaceful protests over violent ones. First, we argue that higher education provides students with higher levels of human capital, as well as access to social capital which allow protests to be more successful.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…At the same time, past studies (Sawyer and Korotayev, 2022) lead us to believe that there may be a qualitative difference between the forms that this protests activity takes; we propose an original theory as to why students would be more likely to join peaceful protests over violent ones. First, we argue that higher education provides students with higher levels of human capital, as well as access to social capital which allow protests to be more successful.…”
Section: Discussionmentioning
confidence: 89%
“…Those with lower income and educational attainment are characterized by lower of all forms of participation on average, primarily due to the barriers to participation that education would otherwise help them overcome (Teixeira, 1992), and a general apathetic disposition to the political process (Gaventa, 1982). That said, as past research has shown, societies without high levels of educational attainment are not devoid of political protests, but instead, they are of a qualitatively different form: violent rebelling and rioting (Beissinger, 2022;Sawyer and Korotayev, 2022;Ustyuzhanin et al, 2022).…”
Section: Students Universities and The Propensity For Political Protestmentioning
confidence: 99%
See 1 more Smart Citation
“…Turning to the main point, reviewed studies see a clear connection between the level of education and the choice of tactics for nonviolent resistance by the protesters, but this hypothesis has not been tested. Previous researchers found a consistent relationship between the likelihood of a peaceful protest and education (Machado, Scartascini and Tommasi 2011;Brancati 2014;Butcher and Svensson 2016;Kostelka and Rovny 2019;Korotayev et al 2020;Sawyer and Korotayev 2021), but they did not investigate how education influences the choice of tactics of the protesters.…”
mentioning
confidence: 96%
“…Thus, education has a pacifistic effect, because it increases the level of human capital, reduces the relative costs of organizing protests leading to an increase in the likelihood of peaceful revolutionary protests (Brancati 2014;Sawyer and Korotayev 2021), and makes violence unacceptable on the personal level, instilling in people a tendency to tolerance (Jenkins and Wallace 1996). In general, it is confirmed by empirical studies: researchers find that the average number of years of schooling is positively and significantly associated with the level of peaceful protests (Brancati 2014;Butcher and Svensson 2016;Korotayev, Bilyuga, and Shishkina 2018;Korotayev et al 2020;Kostelka and Rovny 2019;Machado, Scartascini and Tommasi 2011;Sawyer and Korotayev 2021). But at the same time, it is negatively associated with the likelihood of a civil war, which appears as an extreme form of violent revolutionary conflict (Collier 2004;Barakat and Urdal 2009).…”
mentioning
confidence: 99%